Infrared absorption of gaseous c-ClCOOH and t-ClCOOH recorded with a step-scan Fourier-transform spectrometer - Chu, Li-Kang; Lee, Yuan-Pern (My University, 2009)
Two conformers of ClCOOH were produced upon irradiation at 355 nm of a gaseous flowing mixture of Cl(2), HCOOH, and N(2). A step-scan Fourier-transform infrared spectrometer coupled with a multipass absorption cell was utilized to monitor the transient spectra of ClCOOH. Absorption bands with origins at 1808.0 and 1328.5 cm(-1) are attributed to the C=O stretching and COH bending modes of t-ClCOOH, respectively; those at 1883.0 and 1284.9 cm(-1) are assigned as the C=O stretching and COH bending modes of c-ClCOOH, respectively. These observed vibrational wavenumbers agree with corresponding values for t-ClCOOH and c-ClCOOH predicted with B3LYP/aug-cc-pVTZ density-functional theory and the observed rotational contours agree satisfactorily with simulated bands based on predicted rotational parameters. The observed relative intensities indicate that t-ClCOOH is more stable than c-ClCOOH by similar to 3 kJ mol(-1). A simple kinetic model is employed to account for the production and decay of ClCOOH.
Keywords: density functional theory; Fourier transform spectra; infrared spectra; molecular configurations; organic compounds; rotational states; vibrational states